Holistic Approach in Strengthening Social Resilience in Drug-Prone Areas : Case Study in Pulau Negara - Ade Aryanti Fahriani; Stanislaus Riyanta; Renny Nurhasana (Universitas Negeri Yogyakarta, 2025)
Drug trafficking and substance abuse represent significant challenges, particularly in regions highly vulnerable to these issues. Pulau Negara, identified as a drug-prone area within Hulu Sungai Selatan Regency, frequently experiences incidents of illicit drug trafficking and abuse. The persistence of these drug-related activities can be attributed to the community's insufficient social resilience. This study aims to (1) analyze the current state of social resilience in Pulau Negara; (2) identify the multilevel vulnerability factors contributing to this issue; and (3) propose strategies to enhance the community's resilience against drug-related threats. The findings reveal that social resilience in Pulau Negara is critically weak, influenced by a range of vulnerabilities at the individual, family, and community levels. Key factors include economic pressures, peer influence, unstable family structures, and a lack of supportive community infrastructure. The proposed strategies adopt a comprehensive approach, encouraging collaboration among stakeholders such as local authorities, law enforcement, and community leaders to build a more resilient social framework. By addressing these vulnerabilities holistically, the recommended interventions aim to reduce the community's susceptibility to drug-related activities and promote sustainable social resilience.